2022
DOI: 10.1111/epi.17313
|View full text |Cite
|
Sign up to set email alerts
|

Association between social deprivation and incidence of first seizures and epilepsy: A prospective population‐based cohort

Abstract: Objective: Epidemiologic studies have investigated whether social deprivation is associated with a higher incidence of epilepsy, and results are conflicting, especially in children. The mechanisms underlying a potential association are unclear.This study examines whether there is an association between social deprivation and the incidence of first seizures (unprovoked and provoked) and new diagnosis of epilepsy by comparing incidence across an area-level measure of deprivation in a population-based cohort.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
(94 reference statements)
3
13
0
Order By: Relevance
“…It has been shown that disadvantage is a substantial factor of relevance in child and adult epilepsy and is linked to the incidence and prevalence of epilepsy. [42][43][44][45][46][47][48] We show evidence here that it also plays a role in neurobehavioral status. It is important to note, however, that these findings do not negate the finding that brain structural and connectivity factors as well as the underlying epilepsy disorder play a significant role in neurobehavioral status.…”
Section: F I G U R E 1 Neurobehavior Scores (Child Behavior Checklist...supporting
confidence: 56%
See 3 more Smart Citations
“…It has been shown that disadvantage is a substantial factor of relevance in child and adult epilepsy and is linked to the incidence and prevalence of epilepsy. [42][43][44][45][46][47][48] We show evidence here that it also plays a role in neurobehavioral status. It is important to note, however, that these findings do not negate the finding that brain structural and connectivity factors as well as the underlying epilepsy disorder play a significant role in neurobehavioral status.…”
Section: F I G U R E 1 Neurobehavior Scores (Child Behavior Checklist...supporting
confidence: 56%
“…Our findings presented here extend our understanding of the impact and role of disadvantage in the epilepsy literature, which is consistent with health care outcome findings in multiple other disorders including asthma, autism, COVID-19, diabetes, and sleep health. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Examining the influence of disadvantage at the time of diagnosis as well as at 18 and 36 months later, we find that behavior problems, as rated by parents, the child's teacher, and the child with seizures him-/herself, all indicate that behavioral risk increases with greater social disadvantage. This unanimity of effect, across all informants, with the consistency of relationship over time, points to the robustness and reliability of the effect of disadvantage.…”
Section: F I G U R E 1 Neurobehavior Scores (Child Behavior Checklist...mentioning
confidence: 83%
See 2 more Smart Citations
“…Epilepsy is more prevalent among individuals in lower (more disadvantaged) socioeconomic groups, independent of social drift and other known epilepsy risk factors. [8][9][10] Furthermore, individuals with epilepsy are more likely to live in households with the lowest annual incomes. 11 By contrast, over the past decade, research on the social determinants of health has grown exponentially and suggests that social factors are a fundamental cause of health and disease.…”
mentioning
confidence: 99%